2021
DOI: 10.1302/0301-620x.103b5.bjj-2020-1777.r1
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications of total en bloc spondylectomy for spinal tumours

Abstract: Aims To evaluate the perioperative complications associated with total en bloc spondylectomy (TES) in patients with spinal tumours, based on the extent and level of tumour resection. Methods In total, 307 patients who underwent TES in a single centre were reviewed retrospectively. There were 164 male and 143 female patients with a mean age at the time of surgery of 52.9 years (SD 13.3). A total of 225 patients were operated on for spinal metastases, 34 for a malignant primary tumour, 41 for an aggressive benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
0
28
0
2
Order By: Relevance
“…This significantly reduced the amount of bleeding during surgery. In this report, the operation time was 280 min, shorter than that of Melcher et al ., 14 who reported at 9.2 ± 3.1 h (range 5.3–16.4 h), and the intraoperative bleeding was 900 ml, which was shorter than that of 2000 ml reported by Demura and colleagues 15 ; (2) We detached the paraspinal muscles under periosteum that not only significantly reduced intraoperative bleeding and blood transfusion but also avoided the massive hemorrhage and blood transfusion that could induce internal disorders and diffusive intravascular coagulation. The current patient exhibited no such complications; (3) Modified total en bloc resection was applied to cut the anterior vertebral body, which was a simple and ingenious design to avoid the complications of spinal cord injury; (4) Motor and somatosensory evoked potential was used during the operation to detect the traction and injury of the spinal cord time, and reduce the recovery time; (5) A double‐lumen endotracheal tube was used to control respiration, and can be good to deal with the emergency during operation.…”
Section: Discussionmentioning
confidence: 71%
“…This significantly reduced the amount of bleeding during surgery. In this report, the operation time was 280 min, shorter than that of Melcher et al ., 14 who reported at 9.2 ± 3.1 h (range 5.3–16.4 h), and the intraoperative bleeding was 900 ml, which was shorter than that of 2000 ml reported by Demura and colleagues 15 ; (2) We detached the paraspinal muscles under periosteum that not only significantly reduced intraoperative bleeding and blood transfusion but also avoided the massive hemorrhage and blood transfusion that could induce internal disorders and diffusive intravascular coagulation. The current patient exhibited no such complications; (3) Modified total en bloc resection was applied to cut the anterior vertebral body, which was a simple and ingenious design to avoid the complications of spinal cord injury; (4) Motor and somatosensory evoked potential was used during the operation to detect the traction and injury of the spinal cord time, and reduce the recovery time; (5) A double‐lumen endotracheal tube was used to control respiration, and can be good to deal with the emergency during operation.…”
Section: Discussionmentioning
confidence: 71%
“…The incidence of IF after TES in this study was as high as those in previous reports. [7][8][9][10][11][12][13] Although previous studies showed that most IFs were posterior instrument breakage, the mechanism and preceding condition had not yet been investigated in detail. [8][9][10]12,14 In our study, most IFs after TES were rod fractures preceded by CS and following kyphotic enhancement of the reconstructed level.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, the incidence of instrumentation failure (IF) after TES is high (20% to 40%) due to the destabilization of all three columns of the affected spine. [7][8][9][10][11][12][13] Several studies have focused on IF after TES, and established certain risk factors such as perioperative radiotherapy, TES in the lumbar spine, multiple vertebral body resection, high BMI, inappropriate cage position, and large cage subsidence (CS). [8][9][10]13,14 However, most of these studies have small sample sizes, and only a few have conducted a multivariate risk factor analysis using a sufficient sample size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1990s, Tomita et al reported on total en bloc spondylectomy (TES), which aimed to achieve a complete resection of spinal tumors while reducing the risk of tumor recurrence and complications ( Figure 1 ) [ 12 ]. However, spondylectomy is still an extraordinary type of surgery among general spine surgeons, and several authors have reported a higher rate of perioperative complications [ 13 , 14 , 15 , 16 ]. Improvements in TES surgical techniques over the years have enabled surgeons to achieve good outcomes with lowered significant complications [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%